Production of Yoghurt Shiitake (Yoshitake) as a Dairy-Based Nutraceutical Food - Indratininingsih .; Widodo .; Siti Isrima Oktavia Salasia; Endang Wahyuni (Jurnal Teknologi dan Industri Pangan, 2004)
The objective of this project was to produce shiitake-containing yoghurts as nutraceutical food. Preliminary analysis was conducted to measure nutrient contents of shiitake followed by evaluation of shiitake’s addition on the growth of yoghurt bacteria and probiotics. Yoghurt fermentation was conducted at 420C until pH reached 4.5. Culture starter used were Lactobacillus bulgaricus, Streptococcus thermophillus and Lactobacillus casei with proportion of 1:1:1. During fermentation, acidification rate, pH, titratable acidity, total of yoghurt bacteria, total of probiotics, and concentration of lentinan in the products were measured. The result showed that shiitake powder contains crude protein (22.35%), starch (16,66%), fat (11,56%), ash (7.73%), dry matter (87.57%), dietary fibre (33.35%) and unsoluble dietary fibre (5.45%). The result also showed that supplementation of 4% shiitake powder support the growth of probiotics L. casei and resulting in growth optimum at 1.26 x 109 cells/ml and 2.86 x 109 cells/ml after incubation of 6 and 10 hours respectively. Time needed to reach pH 4.5 of yoghurt supplemented with 4% shiitake powder was achieved after 7 hours of incubation as compared to 8 hours for the unsupplemented one. Total number of probiotics after fermentation of yoghurt with 4% shiitake was higher (7.16 x 109 cells/ml) as compared to the control at 5.3 x 109 cells/ml. Lentinan analysis in yoghurt showed that supplementation 4% of shiitake powder resulted in the highest lentinan accumulation at 22.8% compared with 2.3% for control and 2.9% for 2% shiitake supplementation. It can be concluded that yoghurt shiitake could be applied as nutrient food due to its high nutritious and lentinan content in the product. Key words : Yoghurt, shiitake, nutraceutical food